Situational Analysis of Risk Management for Postpartum Hemorrhage, Chiangrai Prachanukroh Hospital - Punkaew , Supihcha; Nantsupawat, Apiradee; Thungjaroenkul , Petsunee (Nursing Journal CMU, 2020)
Risk management in the health service system aims to identify, evaluate, and take corrective action against potential risks that could lead to patient injury. The objectives of this study were to describe the risk management situation, explore the problems and barriers to risk management, and explore ways to solve problems related to risk management for postpartum hemorrhage at Chiangrai Prachanukroh Hospital. The participants included 8 risk management committee team members of the obstetric department, including the nursing director, 17 professional nurses, and 9 nurse aides from the labour room. Data were collected through questionnaire, interview, and brainstorming. Data were analyzed using descriptive statistics and content analysis. 1. Risk management for postpartum hemorrhage at Chiangrai Prachanukroh Hospital is presented using domains in Supachutikul’s risk management process (2000): 1.1 Risk identification: Perception of risk management with regards to risk identification was at a high level. 1.2 Risk assessment or risk analysis: Perception of risk management with regards to risk assessment/analysis was at a high level. 1.3 Action to manage risk: Perception of risk management with regards to actions to manage risk was at a high level. 1.4 Evaluation: Overall, participants perceptions of risk management at their institutions were at a high level. 2. The problems and barriers related to risk management included incomplete incident records, delayed incident reviews, lack of experience in conducting assessments and following the guidelines, delayed incident reporting in the intranet system, a complex and unstable reporting system via intranet, insufficient training, fear from staff in reporting incidents. 3. The participants’ made the following suggestions for solving problems: the timeline for reviewing incidents should be clear and consistent, a confidential incident reporting system should be developed and risk management staff trainings should be promoted., Participants also suggested improving the incident reporting system, developing an incident reporting channel, and promoting positive attitudes towards incident reporting.